Polyphonic manifestations of pedagogy: Epilog(s) that interrupt sense(s) (Praxis Educativa, 2018)
We propose four irruptions as an epilogue, they seek tensions and meanings in relation to the task of education and pedagogy that, as a conceptual record, offers us lines to inhabit and think about the world in which we live, but also the one we would like to live. Multiple claims and recipes resonate for education in the digital age. Since the end of the last century, education policies have moved between two vertices: crisis and reforms. Reforms of schooling that have been launched in the most diverse countries and regions that make up the globalized world promising answers to this question. It is in this climate of time that Biesta and Säfström propose their manifesto for education where, as they point out, moving between what is and what is not, has become the crossroads for contemporary schooling. Probably, this image is one of the most global in the globalized world. Of course, its effects and local affections are multiple and diverse. This dossier is installed there: to inhabit the educational word, to ask about it. This calls for the imperative need to be manifested by education in a way that allows us to escape a duality that has done nothing but undermine the school without offering lines with which to weave other plots. Interrupting is also the challenge for a theory of education that tries to escape to the crossroads by staying in tension, destabilizing the future by recognizing its openness, opening the possibility to different future potentials.
Keywords: pedagogy; future; condition; interrupt; schooling crisis